SOSIALISASI BERINTERNET SEHAT DAN AMAN PADA REMAJA DI SEKOLAH SMP MUHAMMADIYAH 7 SURAKARTA - Muhlizardy Muhlizardy; Layli Nur A; Wahyu Miranti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Based on the results of interviews with students at Muhammadiyah 7 Surakarta Junior High School, it was found that 7 out of 10 teenagers use the internet almost every day from waking up to sleeping again with frequent online hours. A total of 5 teenagers out of 10 students are students using the internet to play online games. The purpose of this activity is to increase the knowledge of teenagers about healthy and safe internet surfing. The results of this socialization activity took place seen the enthusiastic faces of the youth who followed the presentation given. Occasionally, some teenagers ask things that are considered interesting, such as interesting sites and social media that can be visited and have positive content but are light in accessing data because not all teenagers have fast internet access.